Notary’s Liability in Drafting Successive Powers of Attorney: Case Study of Supreme Court Decision No.130/Pdt.G/2023/PN.Skt - Khusna, Maulidiana Khoiru; Firdaus, Sunny Ummul; Santoso , Bambang (MAQASIDI: Jurnal Syariah dan Hukum, 2025)
The notary occupies a vital role within Indonesia’s civil law system, holding public authority to produce authentic deeds that carry legally binding effects. This responsibility is essential for ensuring legal certainty and fairness in civil transactions. Nonetheless, the practice of issuing successive powers of attorney where the delegated authority is transferred to a third party without the principal’s explicit approval presents significant legal and ethical challenges. This study employs a normative juridical method to examine the scope of notary liability , drawing on statutory provisions, doctrinal analysis, and relevant court decisions. The results indicate that such successive delegation is incompatible with Article 1814 of the Indonesian Civil Code, which enshrines the personal and nontransferable nature of mandates. Moreover, a notary who fails to confirm the legitimacy and consent of the involved parties may face civil, administrative, and ethical sanctions. Applying the prudential principle is therefore imperative to uphold professional integrity and maintain public confidence. Enhancing verification procedures and promoting continuous ethical awareness among notaries are crucial strategies for safeguarding the credibility of authentic deeds and reinforcing legal certainty in Indonesia’s dynamic legal environment.